A novel deletion mutation in ASPM gene in an Iranian family with autosomal recessive primary microcephaly - AKBARIAZAR, Elinaz; EBRAHIMPOUR, Mohammad Reza; AKBARI, Saeedeh; ARZHANGHI, Sanaz; ABEDINI, Seydeh Sedigheh; NAJMABADI, Hossein; KAHRIZI, Kimia (Iranian Journal of Child Neurology, 2013)
How to Cite This Article: Akbarizar E, Ebrahimpour M, Akbari S, Arzhanghi S, Abedini SS, Najmabadi H, Kahrizi K. A Novel Deletion Mutation in ASPM Gene in an Iranian Family with Autosomal Recessive Primary Microcephaly. Iran J Child Neurol. 2013 Spring;7(2):23-30. Objective Autosomal recessive primary microcephaly (MCPH) is a neurodevelopmental and genetically heterogeneous disorder with decreased head circumference due to the abnormality in fetal brain growth. To date, nine loci and nine genes responsible for the situation have been identified. Mutations in the ASPM gene (MCPH5) is the most common cause of MCPH. The ASPM gene with 28 exons is essential for normal mitotic spindle function in embryonic neuroblasts. Materials & Methods We have ascertained twenty-two consanguineous families with intellectual disability and different ethnic backgrounds from Iran. Ten out of twenty-two families showed primary microcephaly in clinical examination. We investigated MCPH5 locus using homozygosity mapping by microsatellite marker. Result Sequence analysis of exon 8 revealed a deletion of nucleotide (T) in donor site of splicing site of ASPM in one family. The remaining nine families were not linked to any of the known loci. More investigation will be needed to detect the causative defect in these families. Conlusion We detected a novel mutation in the donor splicing site of exon 8 of the ASPM gene. This deletion mutation can alter the ASPM transcript leading to functional impairment of the gene product. References 1. Pattison L, Crow YJ, Deeble VJ, Jackson AP, Jafri H, Rashid Y, et al. A Fifth Locus for Primary Autosomal Recessive Microcephaly Maps to Chromosome 1q31. Am J Hum Genet 2000;67(6):1578-80. 2. Darvish H, Esmaeeli-Nieh S, Monajemi G, Mohseni M, Ghasemi-Firouzabadi S, Abedini S, et al. A clinical and molecular genetic study of 112 Iranian families with primary microcephaly. Journal of Medical Genetics 2010;47(12):823-8. 3. Tolmie JL, M M, JB S, D D, JM C. Microcephaly: genetic counselling and antenatal diagnosis after the birth of an affected child. Am JMed Genet 1987;27583-94. 4. Cowie V. The genetics and sub-classification of microcephaly. J Ment Defic Res 1960;4:42-7. 5. Woods C. Human microcephaly. Curr Opin Neurobiol 2004;14(1):112-7. 6. Kaindl AM PS, Kumar P, Kraemer N, Issa L, Zwirner A, Gerard B, Verloes A MS,et al.Many roads lead to primary autosomal recessive microcephaly. Prog Neurobiol 2010;90:363-83. 7. Kumar A BS, Babu M, Markandaya M, Girimaji SC. Genetic analysis of primary microcephaly in Indian families: novel ASPM mutations. Clin Genet 2004;66:341-8. 8. Jackson AP, Eastwood H, Bell SM, Adu J, Toomes C, Carr IM, et al. Identification of microcephalin, a protein implicated in determining the size of the human brain. The American Journal of Human Genetics 2002;71(1):136-42. 9. Roberts E, Jackson AP, Carradice AC, Deeble VJ, Mannan J, Rashid Y, et al. The second locus for autosomal recessive primary microcephaly (MCPH2) maps to chromosome 19q13. 1-13.2. European journal of human genetics: EJHG 1999;7(7):815. 10. Kousar R, Hassan MJ, Khan B, Basit S, Mahmood S, Mir A, et al. Mutations in WDR62 gene in Pakistani families with autosomal recessive primary microcephaly. BMC neurology 2011;11(1):119. 11. Evans PD, Vallender EJ, Lahn BT. Molecular evolution of the brain size regulator genes CDK5RAP2and CENPJ. Gene 2006;375:75-9. 12. Nagase T, Nakayama M, Nakajima D, Kikuno R, Ohara O. Prediction of the coding sequences of unidentified human genes. XX. The complete sequences of 100 new cDNA clones from brain which code for large proteins in vitro. DNA research 2001;8(2):85-95. 13. Jamieson CR GC, Abramowicz MJ. Primary autosomal recessive microcephaly: homozygosity mapping of MCPH4 to chromosome 15. Am J Hum Genet 1999;65:1465-9. 14. Genin A, Desir J, Lambert N, Biervliet M, Van Der Aa N, Pierquin G, et al. Kinetochore KMN network gene CASC5 mutated in Primary Microcephaly. Human molecular genetics 2012. 15. Bond J, Roberts E, Mochida GH, Hampshire DJ, Scott S, Askham JM, et al. ASPM is a major determinant of cerebral cortical size. Nature genetics 2002;32(2):316-20. 16. Fish JL, Kosodo Y, Enard W, Pääbo S, Huttner WB. Aspm specifically maintains symmetric proliferative divisions of neuroepithelial cells. Proceedings of the National Academy of Sciences 2006;103(27):10438-43. 17. Leal G, Roberts E, Silva E, Costa S, Hampshire D, Woods C. A novel locus for autosomal recessive primary microcephaly (MCPH6) maps to 13q12.2. Journal of Medical Genetics 2003;40(7):540-2. 18. Kumar A. Mutations in STIL, encoding a pericentriolar and centrosomal protein, cause primary microcephaly. The American Journal of Human Genetics 2009;84(2):286-90. 19. Hussain MS, Baig SM, Neumann S, Nurnberg G, Farooq M, Ahmad I, et al. Atruncating mutation on CEP135 causes primary microcephaly and disturbed centrosomal function.AMJ,HumGenet 2012;90:871-8. 20. Guernsey DL, Jiang H, Hussin J, Arnold M, Bouyakdan K, Perry S, et al. Mutations in centrosomal protein CEP152 in primary microcephaly families linked to MCPH4. The American Journal of Human Genetics 2010;87(1):40-51. 21. Gul A, Hassan MJ, Mahmood S, Chen W, Rahmani S, Naseer MI, et al. Genetic studies of autosomal recessive primary microcephaly in 33 Pakistani families: novel sequence variants in ASPM gene. Neurogenetics 2006;7(2):105-10. 22. Roberts E, Hampshire D, Springell K, Pattison L, Y C, Jafri H, et al. Autosomal recessive primary microcephaly: an analysis of locus heterogeneity and phenotypic variation. J Med Genet 2002;39:718–721. 23. Woods CG BJ, Enard W. Autosomal recessive primary microcephaly (MCPH): a review of clinical, molecular, and evolutionary findings. Am J Hum Genet 2005 May;76(5):717-28. 24. Kouprina N, Pavlicek A, Collins NK, Nakano M, Noskov VN, Ohzeki JI, et al. The microcephaly ASPM gene is expressed in proliferating tissues and encodes for a mitotic spindle protein. Human Molecular Genetics 2005;14(15):2155-65. 25. Bond J, Scott S, Hampshire DJ, Springell K, Corry P, Abramowicz MJ, et al. Protein-Truncating Mutations in< i> ASPM Cause Variable Reduction in Brain Size. The American Journal of Human Genetics 2003;73(5):1170-7. 26. Pichon B, Vankerckhove S, Bourrouillou G, Duprez L, Abramowicz MJ. A translocation breakpoint disrupts the ASPM gene in a patient with primary microcephaly. European journal of Human Genetics 2004;12(5):419-21. 27. Garshasbi.M, Motazacker M, Kahrizi K, Behjati F, Abedini S, Nieh S, et al. SNP array-based homozygosity mapping reveals MCPH1 deletion in family with autosomal recessive mental retardation and mild microcephaly. Hum Genet 2006 Feb;118(6):708-15. 28. Jackson A, McHale D, Campbell D, Jafri H, Rashid Y, Mannan J, et al. Primary autosomal recessive microcephaly (MCPH1) maps to chromosome 8p22-pter. Am J Hum Genet 1998 Aug;63(2):541-6. 29. Moynihan L, Jackson A, Roberts E, Karbani G, Lewis I, Corry P, et al. A third novel locus for primary autosomal recessive microcephaly maps to chromosome 9q34. Am J Hum Genet 2000 Feb;66(2):724-7. 30. Bond J, Roberts E, Springell K, Lizarraga S, Scott S, Higgins J, et al. A centrosomalmechanism involving CDK5RAP2 and CENPJ controls brain size. Nat Genet.2005 Apr;37(4):353-5. Nat Genet 2005 Apr;37(4):353-5. 31. Jamieson C, Govaerts C, Abramowicz M, J. Primary autosomal recessive microcephaly: homozygosity mapping of MCPH4 to chromosome 15. Am J Hum Genet. 1999;65:1465-9.